2020
DOI: 10.1111/andr.12749
|View full text |Cite
|
Sign up to set email alerts
|

Male partners of infertile couples with congenital unilateral absence of the vas deferens are mainly non‐azoospermic

Abstract: Background: Men with congenital unilateral absence of vas deferens were reported to be mainly azoospermic, with both unilateral renal absence and mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) but some have neither. Objectives:To assess whether in infertile couples the male partners with congenital unilateral absence of vas deferens are mainly azoospermic men. Material and Methods: Retrospective study in a unique university hospital; reproductive, clinical, CFTR analysis and semina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…As early as 1870, a Swiss surgeon, Reverdin, described unilateral renal absence (URA) in a man with CUAVD and an ipsilateral absence of SV (Reverdin 1870). Since then, numerous studies (Schlegel et al 1996;Casals et al 2000;Weiske et al 2000;Patat et al 2016;Mieusset et al 2017Mieusset et al , 2020 have confirmed that URA is found with CAVDs at a high rate of 5-40%, while the prevalence of URA at birth is nearly 1,000 times lower (4/10,000) (Laurichesse Delmas et al 2017). It is important to note that URA is found twoto-three times more frequently in patients with CUAVD (20-40% of the cases, with URA being predominantly ipsilateral) than in those with CBAVD (5-10% of cases).…”
Section: Definition Of the Cavd (Different Forms) History And Clinimentioning
confidence: 99%
See 4 more Smart Citations
“…As early as 1870, a Swiss surgeon, Reverdin, described unilateral renal absence (URA) in a man with CUAVD and an ipsilateral absence of SV (Reverdin 1870). Since then, numerous studies (Schlegel et al 1996;Casals et al 2000;Weiske et al 2000;Patat et al 2016;Mieusset et al 2017Mieusset et al , 2020 have confirmed that URA is found with CAVDs at a high rate of 5-40%, while the prevalence of URA at birth is nearly 1,000 times lower (4/10,000) (Laurichesse Delmas et al 2017). It is important to note that URA is found twoto-three times more frequently in patients with CUAVD (20-40% of the cases, with URA being predominantly ipsilateral) than in those with CBAVD (5-10% of cases).…”
Section: Definition Of the Cavd (Different Forms) History And Clinimentioning
confidence: 99%
“…Therefore, for approximately a quarter of the iCBAVD patients, the responsibility of CFTR cannot be definitively proven, whereas for CF patients, the two mutated alleles can be characterized in 99% of the cases (Table 1 ). For CUAVDs, 30–50% of the subjects carry at least one CFTR mutation after comprehensive gene scanning, which means that more than half of the CUAVDs are not CFTR- related (Schlegel et al 1996 ; Casals et al 2000 ; Cai et al 2019 ; Mieusset et al 2020 ). The presence of a renal abnormality is very significantly more frequent in CAVD patients in whom only one or no CFTR abnormality has been detected (Augarten et al 1994 ; Schwarzer & Schwarz 2012 ).…”
Section: Genetics Of Cavdmentioning
confidence: 99%
See 3 more Smart Citations